PERAN MEKANISME GOOD CORPORATE GOVERNANCE (GCG) TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE (CSRD) - Aris Setiawan; Ali Afif (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study was conducted to obtain empirical evidence of the role of Good CorporateGovernance (GCG) Mechanisms on Corporate Social Responsibility Disclosure(CSRD). The GCG mechanism is proxied by managerial ownership, institutionalownership, number of commissioners, number of audit committees and independentcommissioners. The population in this study were all listed manufacturingcompanies (IDX) in 2018-2020. Sampling in this study using purposive samplingmethod with a total of 341 samples. Hypothesis testing analysis technique usingmultiple linear regression analysis. The results of this study show that the variableof the good corporate governance mechanism as proxied by managerial ownership,institutional ownership, number of commissioners, number of audit committees andindependent commissioners has a positive and significant effect on corporate socialresponsibility disclosure by the company. However, partially, only managerialownership variables and the number of audit committees have a positive andsignificant effect, while the institutional ownership variables, the number of boardsof commissioners and independent commissioners have no effect